1991
DOI: 10.1159/000147214
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Tomographic Determination of the Cranial Volume of the Dog Applied to Racial and Sexual Differentiation

Abstract: The volume of the cranial cavity of 70 dogs (35 males and 35 females) has been determined in two breeds, the galgo greyhound and the pointer, by radiological techniques (computerized tomography; CT) and biostatistical methods. Each head was submitted to a complete series of transverse tomographic sections taken perpendicularly to the basilar plane, every 5 mm and with a thickness of 5 mm. There is a clear difference between the breeds and the two sexes, with a minimal confidence of 99.95%. The application of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Caudal fossa volume, CC volume, and volume ratio means were significantly different in males and females, being greater in the former. Other authors have reported the difference in the size of the CC between male and female dogs, 21–23 but to the authors' knowledge there are no specific data for the caudal fossa volume and the volume ratio that we describe. Smaller volumes of the posterior fossa and supratentorial cavity were reported in girls than in boys, suggesting that calculating the ratio between the posterior fossa and supratentorial CC volumes may eliminate sex difference in the data 16 .…”
Section: Discussionmentioning
confidence: 55%
“…Caudal fossa volume, CC volume, and volume ratio means were significantly different in males and females, being greater in the former. Other authors have reported the difference in the size of the CC between male and female dogs, 21–23 but to the authors' knowledge there are no specific data for the caudal fossa volume and the volume ratio that we describe. Smaller volumes of the posterior fossa and supratentorial cavity were reported in girls than in boys, suggesting that calculating the ratio between the posterior fossa and supratentorial CC volumes may eliminate sex difference in the data 16 .…”
Section: Discussionmentioning
confidence: 55%
“…4 The CT anatomy can be used not only in diagnostic procedures but also in many biometric researches, which constitutes an immense contribution to the evaluation of breeds. 5,6 Previous anatomical descriptions on the rabbit kidneys were rather superficial. 7,8 Moreover, as there is no study on normal CT anatomy of the rabbit, this study…”
mentioning
confidence: 99%
“…Biometrical studies on anatomy using computed tomography make an important contribution to breed identification (Onar et al., 2002; Regedon et al., 1991) in the era of technological advancements in veterinary anatomy (Choudhary et al., 2023). Specialized software is used to construct 3‐dimensional models of the anatomical region.…”
Section: Introductionmentioning
confidence: 99%